"I die silently inside". Qualitative findings from a study of people living with HIV who migrate to and settle in Canada - Aniela M. dela Cruz; Sithokozile Maposa; San Patten; Inusa Abdulmalik; Patience Magagula; Sipiwe Mapfumo; Tsion Demeke Abate; Andrea Carter; Peggy Spies; Jean Harrowing; Marc Hall; Arfan R. Afzal; et al. (Elsevier, 2022)
We report on qualitative findings from a mixed methods study, examining enacted and internalized stigma during mandatory HIV screening among immigration applicants living with HIV in Canada. Qualitative findings show alignment with characteristics of internalized HIV stigma. We conducted 34 semi-structured interviews, and analyzed the data through thematic analysis, using Intersectionality and the Internalized HIV Stigma Scale as our theoretical and analytical frameworks. Participants described experiences of enacted and internalized HIV stigma in ways that were consistent with the four main domains of stereotypes, disclosure concerns, social relationships, and self-acceptance, but also extended the description of HIV stigma beyond these domains. Experiences of internalized HIV stigma and enacted stigma during the Canadian Immigration Medical Examination could potentially influence individuals' long-term engagement in the HIV care cascade during the process of migration to, and settlement in, Canada. We present recommendations for the broader migrant health research agenda, health and social care providers, and public health policies.